Acute effects of interferon on estrogen receptor function do not involve the extracellular signal-regulated kinases p42mapk and p44mapk. - Flint, A; Abayasekara, DR; Wheeler-Jones, C; Riley, P; Kaluz, S; Kaluzova, M; Sheldrick, E; Fisher, P (2000)
Exposure to type I interferons (IFN) increased estrogen receptor (ER) ligand binding and induced protein kinase C (PKC) translocation within 30 min but had no effect on net incorporation of [32P] into ER in Madin Darby bovine kidney (MDBK) cells. Ligand binding was also increased within 30 min by phorbol ester and the protein phosphatase inhibitor okadaic acid. Mitogen-activated protein (MAP) kinase phosphorylation was initially inhibited between 2 and 30 min and subsequently activated between 30 and 60 min after treatment with IFN. The activatory response was blocked by the PKC inhibitor Ro 31-8220. Following transient transfection with an ERE-CAT reporter construct, IFN increased CAT expression after 6 h but decreased ER ligand binding, transcriptional activity and phosphorylation after 48 h, probably as a result of decreased ER concentrations. The results rule out rapid activation of ER ligand binding through phosphorylation at Ser118 by MAP kinase because (1) the increase in ligand binding preceded activation of MAP kinase, and (2) IFN had no short-term effect on [32P]incorporation or ER transcriptional activity. The rapid effect of IFN on ER ligand binding is postulated to reflect phosphorylation of the receptor at Tyr537 by p56lck, a member of the Src family of PKC-activated tyrosine kinases.